Influence of plant growth-promoting rhizobacteria (PGPR) on blackberry (Rubus glaucus Benth. cv. thornless) growth under semi-cover and field conditions (2018)
This study shows the effect of three plant growth-promoting rhizobacteria (PGPR) strains of the genus Bacillus on blackberry (Rubus glaucus Benth.) development under semi cover and field conditions (cropping systems). Endogenous strain Bacillus subtilis GIBI-200, B. pumilus GIBI-206, its mixture (B. subtilis GIBI-200 + B. pumilus GIBI-206), and commercial strain B. subtilis QTS-713 were compared to conventional mineral fertilization (Control) in each cropping system. Field condition system presented higher values (P0.001) than semi cover in: total number of branches (7.32), number of productive branches (7.0), flowers per raceme (26.2), and the lowest percentage of unproductive branches (6.1%). Significant differences (P0.05) were obtained in total number of branches over time by bacterial strains. Nonetheless, last observation of this variable did not present statistical differences among strains and mineral fertilization. No significant differences were evident in terms of number, length, diameter and flowers in the productive branches regarding to bacterial strains and Control. B. subtilis GIBI-200 + B. pumilus GIBI-206 showed a similar statistical behavior compare to mineral fertilization in the number of clusters (8.3) and percentage of unproductive branches (11.1%). In addition, GIBI-200 + GIBI-206, despite statistical equality, exposed greater values than individual strains. Field condition system remains the most promising alternative for the development of blackberry crop and PGPR acts as biofertilizers achieving effects in the long-term growth of blackberry similar to mineral fertilization. Mixtures of PGPR can produce a synergic effect and new combinations should be evaluated in future studies.